The Effect of a Child Model on Breath-Sounds Examination Skills and Satisfaction on Nursing Students - Silpthai Thamruangrit; Sermsri Santati; Jumpee Granger; Dongruethai Buadong; Jatuporn Thongsri (My University, 2022)
One of nursing students’ auscultation critical skills is listening to a child’s breathing sounds. Previously, learning this skill required a SimBaby, which was insufficient, causing nursing students to lack proficiency. Therefore, a CHIld Model (CHIM), an innovation emulating breathing sounds, has been invented based on Gagné’s learning theory to solve this insufficiency. This article reports on the CHIM invention, consisting of hardware, software, and programming, and its effect on nursing students’ breath-sounds examination skills and satisfaction. First, the CHIM was assessed for quality and satisfaction by experts. The results were good in quality and had the highest satisfaction for application in actual use. Second, the CHIM was assessed for auscultation skills and satisfaction among nursing students. Forty-four junior nursing students participated. Next, they were randomly divided into experimental and control groups. Then, both were taught the same about respiratory problems with the SimBaby, except the experimental group had training with the CHIM. After that, both groups’ auscultation skills and satisfaction in the experimental group were examined. Finally, the statistical analysis showed that after the intervention was applied, learning with the CHIM was better than without, with the highest satisfaction level. As intended, the CHIM can help effectively enhance students’ learning and proficiency.
Keywords: Pediatric nursing; Phonocardiography and Auscultation Techniques